2018
DOI: 10.1186/s13104-018-3293-x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation against intestinal colonization by extended spectrum beta-lactamase producing Enterobacteriaceae: a proof of principle study

Abstract: ObjectiveInfections with multidrug-resistant microorganisms are associated with increased hospitalization, medication costs and mortality. Based on our fecal microbiota transplantation (FMT) experience for Clostridium difficile infection, we treated 15 patients carrying ESBL-producing Enterobacteriaceae (ESBL-EB) with FMT. Seven patients underwent a second FMT after 4 weeks when ESBL-EB remained, amounting to a total number of 22 transplants. The objective was decolonization of ESBL-EB.ResultsThree out of fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 18 publications
2
57
0
Order By: Relevance
“…One week after FMT, 3/8 with carbapenem-resistant Enterobacteriaceae and 3/9 with vancomycin-resistant Enterobacteriaceae had negative rectal swabs. A Dutch uncontrolled cohort study examining FMT for decolonization of ESBL-E carriage in 15 patients showed similar results with 3/15 (20%) patients being negative 4 weeks after FMT [15]. A further uncontrolled study from Poland reported successful eradication of intestinal carriage in 15 out of 20 (75%) patients with haematological disease colonized by CPE, ESBL-E or other MDRO 1 month after FMT [19].…”
Section: Discussionmentioning
confidence: 82%
“…One week after FMT, 3/8 with carbapenem-resistant Enterobacteriaceae and 3/9 with vancomycin-resistant Enterobacteriaceae had negative rectal swabs. A Dutch uncontrolled cohort study examining FMT for decolonization of ESBL-E carriage in 15 patients showed similar results with 3/15 (20%) patients being negative 4 weeks after FMT [15]. A further uncontrolled study from Poland reported successful eradication of intestinal carriage in 15 out of 20 (75%) patients with haematological disease colonized by CPE, ESBL-E or other MDRO 1 month after FMT [19].…”
Section: Discussionmentioning
confidence: 82%
“…Another small retrospective case-matched study of 20 patients in France showed 80% (8/10) of patients cleared CRE or CRE/Acinetobacter colonization 14 days after FMT versus 20% (2/10) in the control group [24]. In other small studies (n = 8 to 20) with various endpoints, the effectiveness of decolonization ranged from 20% to 93% [1,[25][26][27][28][29]. One study by Davido et al suggests that based on an 87% decolonization rate of VRE at three months, FMT should be further explored to combat outbreaks within hospitals [30].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 97%
“…Moreover, the dissemination of ARGs and pathogenic AROs in patients hampers effective medical care of infections and results in longer hospitalization and higher medical expenditures [23]. Still, multiple studies report e cient reduction of ARGs and decolonization of AROs through microbiota transplantation [24,25].…”
Section: Introductionmentioning
confidence: 99%